Biti tu in tam - Juvančič, Katarina (Etnolog. Nova vrsta (Ljubljana), 2009)
The article deals with the theoretical and metaphorical reflection of doing fieldwork at the festivals of folk, traditional and Celtic music in Scotland and stresses the transformative nature of fieldwork experience, dialogic research and ethnographical collaboration between the researcher and the researched. The author also provides a more thorough introduction to the contemporary methodological trend in ethnographic research, initiated by the post-colonialist or post-modern anthropology that is multi-sited ethnography, whilst calling attention to its inadequacies and searching for more appropriate ethnographic model for the research of contemporary social reality and identity construction.
Keywords: Juvančič, Katarina, 1977-; ethnography; etnografija; folk music; ljudska glasba; folk glasba; raziskovanje; terensko delo; glasbeni festivali; Škotska